Credit and House Prices in the Irish Residential Market - Paul Egan; Kieran McQuinn; Conor O'Toole (Intereconomics, 2024)
Many countries experienced a residential credit bubble prior to the global financial crisis; however, by most criteria, the Irish residential and financial sector witnessed one of the most significant imbalances across contemporary western economies. The Irish property market had experienced a significant increase in activity as the economy was transformed during the Celtic Tiger era. However, hand in hand with the increase in housing demand came a major credit market liberalisation, which resulted in a substantial increase in mortgage credit. This, in turn, additionally fuelled the emerging house price bubble by 2005, resulting in the Irish financial sector being especially vulnerable to the global financial crisis of 2007/08 due to its substantial liabilities in the property market. A period of significant reform in credit availability followed, as evidenced by the adoption of the Central Bank of Ireland of macroprudential rules in early 2016. Now, 17 years after the crisis first impacted the Irish market and given the persistent increase observed in Irish house prices since 2012, it is prudent to examine the interrelationship between credit availability and house price movements to see how the residential and financial markets are evolving. This article uses a recently developed model of the Irish housing and credit sector to assess the contribution of changing credit standards to recent house price developments. The developments in the Irish market offer lessons for other EU member states.
Keywords: R21; E51; G12; 330